Penerapan Kaidah Fiqih dalam Penafsiran Ayat-Ayat Ekologi dalam Tafsir Marah Labid - Aqib Zuhri Adi Kusuma; Husein Aziz; Muhtarom Ali (Jurnal Studi Al-Qur'an, 2025)
In today's digital world, cyberbullying has become a severe issue, especially among teenagers, which can negatively impact their mental health and identity. This study explores the application of fiqh principles in interpreting ecological verses in Tafsir Marah Labid by Imam Nawawi al-Bantani. The methodology used is a qualitative approach with content analysis, focusing on identifying and interpreting fiqh principles in an environmental context. The results show that Imam Nawawi al-Bantani indirectly applies fiqh principles such as “la darara wa la dirar” and “al-masyaqqah tajlibu al-taysir” in explaining environmental verses. This interpretation highlights the importance of maintaining ecological balance as a human responsibility as a caliph. The fiqh approach in Tafsir Marah Labid is highly relevant to current environmental conservation efforts and the importance of Islamic values education for ecological preservation among the younger Muslims.